Post‐fire regeneration in Mediterranean reforested sites as affected by mechanical site preparation: lessons for restoration. Issue 4 (6th March 2013) - Hibsher, Nurit; Moshe, Yossi; Bney‐Moshe, Eitan; Ben‐Moshe, Ezra; Zangi, Ela; Zuck, Aviram; Osem, Yagil
Abstract: Question: The importance of silvicultural site preparation techniques in determining vegetation succession is increasingly recognized. We studied the effects of mechanical site preparation (MSP) on post‐fire vegetation regeneration within reforested sites in Mediterranean Israel. Location: Upper Galilee region, Israel. Methods: Vegetation cover and composition, ruderal species colonization and pine regeneration were monitored in four reforested sites for 3 yr following wildland fires that burned mature Pinus brutia and P. halepensis plantations. In each reforested site, a 50 m × 50 m monitoring area was assigned and measurements were conducted within five subplots (2 m × 50 m) encompassing three MSP patch types: ploughed patches (P), unploughed patches (UP) and planting mounds (M) that combined ploughing, pit digging and wood‐chip mulching. Results: Recovery of vegetation cover (excluding pines) was rapid. The MSP patch type significantly affected vegetation cover in the first spring following the fire: cover was lowest on M, intermediate on P and highest on UP. However, these differences became minor by the third spring following the fire. Total woody species richness was not affected by MSP patch type, although there were minor effects on relative abundance of woody species. Two ruderal species were found, but their abundance became untraceable by the third year. Patterns of MSP effects on pine regeneration were similar for P. halepensis and P. brutia . Density of emerging seedlings of both pine species during the first year following the fire was significantly affected by MSP patch type: lower in P and M than in UP by more than 50% and 90%, respectively. However, emergence and/or survival during the following 2 yr was higher in P and M than in UP, with overall outcome of pine regeneration still about 50% lower in P and M than in UP. Conclusions: The MSP treatments had only a minor, short‐term effect on post‐fire regeneration and colonization of vegetation, except for pine recruitment, which was more severely affected. Abstract : Biria forest, November 2006, following the wildland fire which occurred in the previous summer (August). Salvage logging was already applied in part of the burned area.